ASUHAN KEBIDANAN KOMPREHENSIF PADA NY. H DI KLINIK UTAMA LESTARI TEMBILAHAN TAHUN 2022 - Yuliana, Yuliana (STIKES HUSADA GEMILANG, 2023)
Comprehensive midwifery care is care provided by midwives from the start of pregnancy, childbirth, newborns, postpartum, and the use of family planning which aims to provide quality services to prevent the occurrence of AKI and IMR. The Objectic To be able to provide comprehensive midwifery care using Varney's line of thought and documented in SOAP form. The Methods Midwifery management approach method with Varney's line of thought and documented in the form of SOAP, carried out at the Utama Lestari Clinic on March 12-7 May 2022. This midwifery care was carried out on Mrs.